Optimalisasi Resapan Air melalui Biopori di Rumah Tipe 36 - Rizqiyah, Umara Hasmarani; Marsa, Ivan Fachrul; Taufik, Yusaumi Ramadhanti Fitri; Ismajaya, Muh. Aryanugraha; Afiah, Indah Nur (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Waterlogging in subsidized housing areas often occurs due to low soil infiltration capacity, increasing rainfall intensity, and limited environmental drainage systems. This community service activity aims to implement biopore technology as a simple solution to improve rainwater infiltration in a Type 36 house at Bumi Findaria Mas 2 Housing, Moncongloe, South Sulawesi. The method included community outreach and the direct application of biopore technology through the construction of five infiltration holes using 4-inch diameter pipes. The implementation stages consisted of hole excavation, pipe installation, and filling the holes with organic materials as infiltration media. The results show that the installation of five biopore units increased soil water absorption and has the potential to reduce waterlogging in residential areas. The outputs of this activity include the installation of biopores and increased community understanding of environmental management and the use of organic waste as infiltration media. This technology has the potential to be applied sustainably in dense housing areas.